Eksplorasi Limbah Tulang Sapi Sebagai Sumber Biomaterial Hidroksiapatit - Alimuddin Alimuddin; Susi Rahayu (Kappa Journal, 2022)
The abundance of cow bone waste in West Nusa Tenggara has not been in line with proper treatment. Cow bones contain a lot of apatites that can be modified into raw materials for the fabrication of hydroxyapatite. The need for hydroxyapatite as bone graft biomaterials increase in Indonesia continuously. The study aims to identify the appropriate preparation method for extracting hydroxyapatite from cow bone. Mechanical and thermal techniques are used to extract the cow bone. The method utilizes heat energy and mechanical energy to achieve hydroxyapatite. The extracted powder from cow bone was identified the ratio of Ca/P using EDX, calculated the yield of the fabricated product, measured its bulk density, and placed its functional group by FTIR. The results reveal that the best preparation method to acquire hydroxyapatite is by extracting the compact bone of bovine. The compact bone is macerated with alcohol for 12 hours and calcined at a temperature of 9500C for three hours. The apatite has a Ca/P ratio of 2.25, yielding 66.53%, and a bulk density of 1.18 g/cm3. Typical hydroxyapatite groups that emerge from apatite powder are the presence of functional groups OH, PO43-, and CO32-. This preparation method also has powders with unidentified C-H functional groups. The fact of this variety indicates the powder does not contain organic elements that can be at risk of rejection by the human body. Therefore, the apatite extracted from cow bone can be used as a safe biomaterial for the human body.